Iris recognition based on robust iris segmentation and image enhancement. (20th December 2011) - Verma, Abhishek; Liu, Chengjun; Jia, Jiancheng
A new iris recognition method based on a robust iris segmentation approach is presented in this paper for improving iris recognition performance. The robust iris segmentation approach applies power-law transformations for more accurate detection of the pupil region, which significantly reduces the candidate limbic boundary search space for increasing detection accuracy and efficiency. The limbic circle having a centre within close range of the pupil centre is selectively detected, and the eyelid detection approach thus leads to improved iris recognition performance. Experiments using the Iris Challenge Evaluation (ICE) database show the effectiveness of the proposed method.